Physicochemical and Nutritional Properties of Functional Fresh Pasta With Free and Microencapsulated Olive Pomace Extract - Giuseppe Natrella; Mariana Miccolis; Giusy Rita Caponio; Alessandro Di Michele; Lilia Zago; Carla Di Mattia; Graziana Difonzo (Food Frontiers)
ABSTRACT The increased demand of consumers for healthy foods has generated interest among researchers and food producers in developing functional foods. Olive pomace (OP) can be used to obtain high‐added value products, being a valuable source of phenols. The aim of the study was to assess the influence of incorporating OP extract, as free lyophilized (F‐OPE) and as microencapsulated (M‐OPE), on the physicochemical, nutritional, and sensory properties of fresh pasta “cavatelli.” Pasta samples with M‐OPE were characterized by a higher yellow color and had higher total phenolic compounds content compared to samples with F‐OPE (on average 0.43 vs. 0.39 mg gallic acid equivalents (GAE) g−1 of fresh sample), showing that the microencapsulation technique preserved polyphenols during pasta manufacturing. The experimental samples had lower moisture (on average 29% vs. 31.14%) and aw compared to the control pasta (CP), but still complied with Italian law, according to which fresh pasta must have at least 24% moisture and aw not higher than 0.97. Microencapsulation proved to be useful in retaining volatile organic compounds, as well as enhancing antioxidant activity. Scanning electron microscopy (SEM) analysis showed that samples with F‐OPE had more porous and spongy structures. On the other hand, the gluten network was lost in pasta sample with the highest content of M‐OPE. The intensity of odor and taste linked with raw cereal was more intense in CP, than in experimental ones. Bitterness and astringency were perceived most in samples with F‐OPE, especially at high concentration. Indeed, considering the overall acceptability, all the samples gained a positive score, except for the sample with the highest F‐OPE content.